Critically ill patients with severe infections related to Geotrichum species: A French retrospective multicentre study. Issue 2 (8th December 2021) - Valade, Sandrine; Picard, Muriel; Mokart, Djamel; Calvet, Laure; Bruneel, Fabrice; de Montmollin, Etienne; Aissaoui, Nadia; Champigneulle, Benoit; Bigé, Naike; Boissier, Florence; Pène, Frédéric; Mayaux, Julien; et al.
Abstract: Objectives: Geotrichum spp can be responsible for severe infections in immunocompromised patients. We aim to describe Geotrichum‐ related infections in the ICU and to assess risk factors of mortality. Methods: Retrospective multicentre study, conducted in 14 French ICUs between 2002 and 2018, including critically ill adult patients with proven or probable infection related to Geotrichum species. Data were obtained from the medical charts. Results: Thirty‐six patients, median age 60 years IQR [53; 66] were included. Most of the patients had haematological malignancies (78%). The reason for ICU admission was shock in half of the patients (n = 19, 53%) and respiratory failure in thirteen patients (36%). Median SOFA score was 8.5 IQR [7; 15]. Time between ICU admission and fungal diagnosis was 2.5 days [−1; 4]. Infection was disseminated in 27 (75%) patients with positive blood cultures in 25 patients (69%). Thirty patients (83%) received curative antifungal treatment in the ICU, in a median time of 1 day [0;1] after ICU admission. Twenty‐four patients (67%) died in the ICU and hospital mortality rate was 69%. The number and extent of organ failures, as represented by SOFA score, were associated with mortality. Conclusions: This study demonstrates poor outcome in critically ill patients with Geotrichum‐ related infections, which encourages a high level of suspicion.